Changes in trophic ecology of fish assemblages after no take Marine Protected Area designation in the southwestern coast of Portugal - Pereira, T.J. (2018)
Changes in fish assemblage structure caused by human activities, such as fishing, can alter trophic relationsin fish assemblages. In this context, Marine Protected Areas (MPA) are efficient tools for habitatrecovery and ideal environments for evaluating changes on the trophic structure resulting from humanactivities. The present work targeted fish assemblages from two no-take MPAs from the northern half ofSouth Alentejo and Costa Vicentina Marine Park, established in 2011. Previous works reported positiveeffects on local fish assemblages after no-take MPA designation, and it is therefore important to furtherstudy its impact on local fish assemblages, especially concerning trophic interactions. Local fish assemblageswere sampled (summer 2011, winter 2012, summer 2013 and winter 2013) using trammelnets. Diets were characterized and digestive tract contents of the 10 most abundant fish species werecompared between the no take MPAs (treatment) and adjacent areas (controls), and changes evaluated asa function of time since protection. Results revealed significant differences between the diets of fish fromprotected and non protected areas, with crabs being the preferential prey in both protected and controlareas but being more ingested outside the no-take areas. However, these differences were evident sincethe beginning of the study. Fish assemblages from the northern area presented significantly larger nichebreadth and significantly increasing with time. This way, the main effects of no-take MPA implementationwere directly visible on the niche breadth but did not directly impact the diet composition ofthe sampled fish assemblages, contributing however to reinforce the already naturally existent differences.This work provides important information regarding the effect of changes in the fish assemblagecaused by MPA designation on the trophic ecology of fish.